Odpowiedzi

Najlepsza Odpowiedź!
2010-03-06T14:29:14+01:00
C) 1 - 0,2x = -0,3x
Przenosimy -0,2x na drugą stronę znaku równości:
1 = -0,3x + 0,2x
1 = -0,1x /* (-10)
-10 = x
x = -10

d) 0,01x - 1 = 0,1 - 0,1
Jeśli to jest dobrze zapisane to:
0,01x - 1 = 0
0,01x = 1 /*100
x = 100
5 3 5
2010-03-06T14:30:04+01:00
C)

1 - 0,2x = -0,3x
-0,2x+0,3x=-1
0,1x=-1
x=-10


d)

0,01x - 1 = 0,1 - 0,1
0,01x=1
x=100

pozdrawiam:)

2 5 2
2010-03-06T14:42:40+01:00
C) 1-0,2x=-0,3x
1=-0,3+0,2x
1=-0,1x/-0,1
x=-10

d)
0,01x-1=0,1-0,1
0,01x=0,1-0,1+1
0,01x=1/0,01
x=100

2 5 2